Pengenalan Model Perumahan Menggunakan Metode Polygonal Modeling Dengan Teknik Extrude Face Berbasis Virtual Reality - Helda Yenni (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
The housing business is currently growing rapidly because the house is one of the basic needs of humans. PT. Pesona Quatraz Lestari is one of the property companies that provide various types of housing. By the results of observations, the information media used is still in the form of 2D images that are not interactive. As the solution, a virtual reality-based system was designed that presents housing model information in 3D. The housing object modeling uses the polygonal modeling method with the extrude face technique. Polygonal modeling is object modeling using points that determine the area of a surface so that it can create planes from a 3D model. While the extrude face technique is a modeling technique in forming new polygons on it. The system runs on the Android platform and is equipped with a mobile stick controller as a navigation tool. This system can provide information in the form of housing models, building materials, housing loan costs (KPR), and housing location information packaged in the form of interactive multimedia elements. The system has gone through the stages of testing and implementation, it can be used as a housing promotion media as an effort to increase the company's competitiveness.